1998
DOI: 10.1063/1.368987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cylindrical geometry on the wet thermal oxidation of AlAs

Abstract: We have investigated the wet thermal oxidation of AlAs in cylindrical geometry, a typical configuration for vertical-cavity surface-emitting lasers. Through both experiment and theoretical calculations, we demonstrate a significantly different time dependence for circular mesas from what has been reported in the literature both in studies of stripes and in a study of circular mesas. We attribute this different time dependence to the effect of geometry on the oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 14 publications
(15 reference statements)
4
14
0
2
Order By: Relevance
“…The difference in O 2 pressure, which is due to the concentration of the oxidizing agent, is the decisive factor in the improvements when the shells are formed in a diffusion-driven process. [23,24] After the initial oxidation of the surface of the GaN nanowire, the whole process is assumed to undergo the following stages (as schematically illustrated in Fig. 4) [23] : diffusion of O 2 through the already oxidized surface of the Ga 2 O 3 layer; a subsequent oxidation reaction at the Ga 2 O 3 / GaN interface; and the accompanying inward growth of the Ga 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in O 2 pressure, which is due to the concentration of the oxidizing agent, is the decisive factor in the improvements when the shells are formed in a diffusion-driven process. [23,24] After the initial oxidation of the surface of the GaN nanowire, the whole process is assumed to undergo the following stages (as schematically illustrated in Fig. 4) [23] : diffusion of O 2 through the already oxidized surface of the Ga 2 O 3 layer; a subsequent oxidation reaction at the Ga 2 O 3 / GaN interface; and the accompanying inward growth of the Ga 2 O 3 layer.…”
Section: Resultsmentioning
confidence: 99%
“…However, until recently, studies of the oxidation process have been concerned primarily with the simpler case of stripes. As demonstrated in several recent reports, [4][5][6] oxidation proceeds much differently in circular mesas than in stripes. It can also be shown that the oxidation process has a unique timedependence for square mesas.…”
Section: Introductionmentioning
confidence: 88%
“…The procedure to implement the model with an anisotropic reaction (and an isotropic diffusion and convection) is based on the iterative use of Eq. (5) to (7) with { �⃗ } defined in (11) and (12). It relies on understanding that the progression of the oxidation front with time is the result of a succession of an ensemble of elementary point-like oxidations of duration, dt, whose local extent around the point, ⃗, in the direction, ϕ, is given by…”
Section: Anisotropic(-reaction) Scenariomentioning
confidence: 99%
“…depend on the geometrical characteristics of the interface between the (unoxidized) semiconductor and the oxidized areas resulting from the partial lateral oxidation of mesas whose etched sidewalls have been exposed to water. To address the above-mentioned requirement and potentially enhance the device manufacturability, several models have been developed to reproduce the process kinetics [12] [13] [14] [15] [16] [17] [18] [15] [19] [20] [21] [22]. These models are, in essence, all based on the empirical model established by Deal and Grove which describes and quantifies the temporal evolution of the oxidation depth of surface oxidized silicon wafers in terms of the interplay between the diffusive and reactive nature of the process [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation